Diskursus Nalar Islam dan Ilmu Pengatahuan dalam Menjelaskan Asal Usul Kehidupan Bumi - EKO NOPRIYANSA (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2020)
Biotransition Theory is a concept of thought and the results of the suitability test by conducting comparative experiments, in questioning the origin theory of earth life which was carried by several previous scientists such as Abiogenesis, Biogenesis, Louis Pasteur's theory, and Nasa's research which until now has not been able to universalize universally. complete with a series of theories that existed before. This paper aims to explain some of the findings and criticisms of previous theories by making a comparative approach to research and studies that the author is currently doing. Aside from being an effort to compare and test the suitability of the development of existing knowledge, this article also explains coherently to Biotransisi theory in terms of various aspects including the results of comparative studies of previous theories that have weaknesses both regarding the rationale to the experiments carried out by several previous scientists. By presenting the results of the experiments and the results of literature review, the steps in this research can answer completely the fundamental questions about the origin of earth's life, so that this paper becomes an important spotlight for various groups to carry out further studies of some of the thoughts set forth in the text this.